YHWH (STUDI GRAM ATIKAL SINTAKSIS TERHADAP KATA YHWH ADALAH EMPAT KONSONAN IBRANI YANG MERUPAKAN SEBUTAN SESEMBAHAN BANGSA ISRAEL) - Bernike Sihombing; David Bunbunan Hasibuan; Ibrahim Feoh (THEOSOPHIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
Abstract YHWH is the four Hebrew consonants also known as the Tetragrammaton, which refer to the deity worshipped by the people of Israel, particularly within the Jewish faith. Therefore, this paper aims to accomplish the following objectives: First, to provide an explanation of what is meant by YHWH; Second, to emphasize the importance for Christians to understand the meaning of YHWH; Third, to explore the various interpretations and equivalents of YHWH in different languages, as well as their meanings based on several translations and the intended significance found in the Bible, both in the Old Testament and the New Testament.  Abstrak YHWH adalah empat konsonon ibrani juga dikenal dengan sebutan Tetragrammaton yang merupakan sesembahan bangsa Israel secara khusus agama Yahudi. Dengan demikian yang akan dicapai dalam penulisan ini, Pertama, memberi penjelasan mengenai apa yang dimaksud YHWH. Kedua, Sebagai umat Kristen penting memahami apa yang dimaksud YHWH. Ketiga, Apa saja yang dimaksud YHWH dan padanannya dalam bahasa lainnya dan pengertiannya sesuai beberapa bahasa terjemahan serta padanan arti yang dimaksudkan dalam Alkitab, baik kitab Perjanjian lama maupun Perjanjian Baru.